A "think coach, think male" phenomenon: women coaches' experiences of development, progression, and retention in coaching within the United Kingdom - Gosai, J.; Jowett, S.; Rhind, D. J. A. (International Sport Coaching Journal, 2024)
Women coaches have remained underrepresented within sports coaching at all levels. Thus, the purpose of this paper was to describe the factors surrounding the development, progression, and retention of women coaches within the United Kingdom. The study involved semistructured interviews with 15 women coaches who were coaching female athletes in team sports. Content analysis of the qualitative data identified barriers and enablers at individual, interpersonal, organisational, and sociocultural levels. Results indicated that women coaches face several barriers because of their gender, which their men counterparts do not often encounter. Practically, individuals and organisations can both take action to reduce damaging stereotypical ideologies that produce challenging predicaments for women within the coaching landscape.